Dynamics and stability of divertor detachment in H-mode plasmas on JET. (5th July 2017) - Field, A R; Balboa, I; Drewelow, P; Flanagan, J; Guillemaut, C; Harrison, J R; Huber, A; Huber, V; Lipschultz, B; Matthews, G; Meigs, A; Schmitz, J; et al.
Abstract: The dynamics and stability of divertor detachment in N 2 seeded, type-I, ELMy H-mode plasmas with dominant NBI heating in the JET ITER-like wall device is studied by means of an integrated analysis of diagnostic data from several systems, classifying data relative to the ELM times. It is thereby possible to study the response of the detachment evolution to the control parameters (SOL input power, upstream density and impurity fraction) prevailing during the inter-ELM periods and the effect of ELMs on the detached divertor. A relatively comprehensive overview is achieved, including the interaction with the targets at various stages of the ELM cycle, the role of ELMs in affecting the detachment process and the overall performance of the scenario. The results are consistent with previous studies in devices with an ITER-like, metal wall, with the important advance of distinguishing data from intra- and inter-ELM periods. Operation without significant degradation of the core confinement can be sustained in the presence of strong radiation from the x-point region (MARFE).